Identification of a diverse mini‐core panel of Indian rice germplasm based on genotyping using microsatellite markers. Issue 2 (17th March 2015) - Tiwari, Kapil K.; Singh, Anshuman; Pattnaik, Sasmita; Sandhu, Maninder; Kaur, Sukhdeep; Jain, Sourabh; Tiwari, Sushma; Mehrotra, Shweta; Anumalla, Mahender; Samal, Rashmita; Bhardwaj, Jyoti; Dubey, Neha; et al.
Abstract Identification of a small core germplasm set representing the available genetic diversity is essential for its proper evaluation and subsequent utilization in rice improvement programmes. For constituting a small diverse mini‐core panel of Indian rice germplasm, a representative set of 6912 accessions drawn based on their geographic origin from the whole rice germplasm collection available in the National Gene Bank was genotyped using 36 microsatellite markers. Automated fragment analysis of amplicons yielded a total of 435 alleles, with an average 12.4 and range of 3–29 alleles per locus. Polymorphism information content (PIC) ranged from 0.08 (RGNMS190) to 0.86 (RM552) with an average of 0.528. Based on genotyping data, a mini‐core consisting of 98 genotypes was identified. Ninety‐four per cent of the alleles present in the core set were present in the mini‐core. The identified small but diverse panel will be useful for further intensive trait‐specific evaluation and utilization in allele mining.